The Structure of Time in Kurdish Folklore Stories - Rokan Gawril Shaiya Marben; Kaify Ahmad Abdulqader (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
This study is entitled "The Structure of Time in Kurdish Folklore Stories". Time as a main and important technique of literary and artistic works, the researcher under this title, has tried to present the importance of Kurdish folklore stories. Through these important structures, which the storyteller has been able to use skillfully and proficiently in stories, he has also been able to deal with the time of events, grow, and change with them properly. What is important in this study is that the researcher has highlighted the important techniques of time, which play a major role in constructing the timing of events and their use by the storyteller. The researcher has also highlighted the techniques of speeding up and slowing down time, which play a role in accelerating and slowing down the narrative time, because there are some phrases, which have been mentioned in the examples of stories, used by the storyteller It has slowed down the time, and sometimes because of these techniques, the narrative time is close to a halt, especially when using the descriptive method, which the researcher has mentioned in this study. Keywords Time, story, view, abbreviation, repetition.